2012
DOI: 10.1590/s0101-28002012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do transplante renal na morfologia e função cardíaca

Abstract: ResumoO envolvimento cardíaco é muito frequente nos portadores de doença renal crônica em diálise. O transplante renal resulta em redução da morbidade e mortalidade em relação aos pacientes em diálise. O objetivo desta revisão foi abordar o efeito do transplante renal na estrutura e função cardíaca avaliada pela ecodopplercardiografia. Desde a década de 1980, os estudos já demonstravam tendência à melhora nos parâmetros cardíacos após o transplante renal. Com a melhora dos métodos de imagens ao ecodopplercardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Most data point toward the persistence of DD after RTx, despite the alleviation of LVH (see above), attributing this unexpected finding to immunosuppressant drugs, hypertension, and pre-RTx myocardial fibrosis. [26][27][28][29]…”
Section: Diastolic Dysfunction (Dd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most data point toward the persistence of DD after RTx, despite the alleviation of LVH (see above), attributing this unexpected finding to immunosuppressant drugs, hypertension, and pre-RTx myocardial fibrosis. [26][27][28][29]…”
Section: Diastolic Dysfunction (Dd)mentioning
confidence: 99%
“…The impact of RTx on DD is not entirely understood, as studies have reported conflicting results. Most data point toward the persistence of DD after RTx, despite the alleviation of LVH (see above), attributing this unexpected finding to immunosuppressant drugs, hypertension, and pre‐RTx myocardial fibrosis …”
Section: Conventional Transthoracic Echocardiography (Tte)mentioning
confidence: 99%